Integrable nonlocal derivative nonlinear Schrödinger equations. (1st June 2022) - Ablowitz, Mark J; Luo, Xu-Dan; Musslimani, Ziad H; Zhu, Yi
Abstract: Integrable standard and nonlocal derivative nonlinear Schrödinger equations are investigated. The direct and inverse scattering are constructed for these equations; included are both the Riemann–Hilbert and Gel'fand–Levitan–Marchenko approaches and soliton solutions. As a typical application, it is shown how these derivative NLS equations can be obtained as asymptotic limits from a nonlinear Klein–Gordon equation.